Recognition And Appreciation And Its Psychological Effect On Job Satisfaction And Performance In A Malaysia IT Company: Systematic Review - Norida, Abdullah; Olurotimi Adebayo, Shonubi; Rahman, Hashim; Norhidayu, Ab Hamid (IOSR Journals, 2016)
There is a general assumption that every employee like to be recognized and appreciated, because they are everyday human innate need. Though, there has been extensive study on intrinsic motivational factors but still there still few studies on appreciation and recognition and how they can be well utilized in the organization to boost job satisfaction of employees. Thus, this paper aims to explore and examine previous literatures on employee intrinsic motivational factors and using those studies as background knowledge for this present study on employees‟ perception of recognition and appreciation and the influence it has on their job satisfaction, performance, productivity and commitment towards the organization goals and objectives. Recognition and appreciation which can also be refers to as intrinsic motivation are basic psychological process, therefore, becoming significance and inevitable to every human. However, this present study aims to utilize survey research method, vast of the constructs that will be used in this study will be operationalized using previously-validated and originally developed measures with little or no modifications where necessary to suit the present research context. Structural equation modeling using Amos will also be utilized to find the level of influence of recognition and as well as the level of appreciation towards TM employees' job satisfaction and performance.